Respiratory Metabolism and Antioxidant Response in Chinese Mitten Crab Eriocheir sinensis During Air Exposure and Subsequent Reimmersion - Bao, Jie; Li, Xiaodong; Xing, Yuenan; Feng, Chengcheng; Jiang, Hongbo (Frontiers in Physiology, 2019)
Chinese mitten crab, Eriocheir sinensis, often suffer from severe air exposure stress during transportation and culture; high mortality occurs due to desiccation. In this study, the effects of air exposure stress (0, 2, 4, 8, and 16 h) and re-immersion (2, 6, 12 h) on respiratory metabolism and antioxidant responses in Chinese mitten crabs were studied under laboratory conditions. The results showed that respiratory metabolism and antioxidant enzyme activities were significantly influenced by air exposure stress. During the air exposure stage, superoxide dismutase (SOD), catalase (CAT), and lactate dehydrogenase (LDH) activities in the gills and hepatopancreas first increased and then decreased as air exposure time increased. All of these parameters were significantly higher in the 4 h air exposure group than those in the control group. All the parameters were significantly lower in the 16 h air exposure group than those in the control group, except LDH in the hepatopancreas. However, succinate dehydrogenase (SDH) activity gradually decreased with increased air exposure time and all the air exposure groups were markedly lower than those in the control group in the gills. During the re-immersion stage, the oxygen consumption rate (OCR), ammonia excretion rate (AER), and oxygen to nitrogen ratio (O:N) restored to normal levels after 12 h re-immersion, except in the 16 h air exposure group, where OCR and O:N were significantly higher than those in the control group and AER was significantly lower than that in the control group. The LDH activity in all groups restored to normal levels after 12 h re-immersion. The SDH, SOD, and CAT activities of the 2 h and 4 h air-exposed groups returned to normal levels after 12 h re-immersion; however, these three parameters were still significantly higher in the 16 h air-exposed group than in the control group in the gills and hepatopancreas. Overall, Chinese mitten crab reduce aerobic respiration and increase anaerobic respiration capacity during desiccation. Under air exposure stress, Chinese mitten crab change their energy utilization mode to meet their energy demands and adjust their respiratory metabolism and antioxidant enzymes activities to adapt to adverse environments.